Radiocontrast Media Hypersensitivity Reactions in Children - Francesca Saretta (Medicina, 2022)
Hypersensitivity reactions to radiocontrast media seem to be rare in children. Furthermore, the use of radiocontrast media in children remains quite safe in terms of the severity of reactions. Since pediatric guidelines are lacking, the diagnostic workup employed in adults could be adapted to children, taking into account that results have not yet been validated in this age group. Specific protocols for risk stratification and management of severe reactions have been proposed so far.